Proceedings of ISIC: The Information Behaviour Conference Pretoria, South Africa, 28th September to 1st October, 2020 2020
DOI: 10.47989/irisic2027
|View full text |Cite
|
Sign up to set email alerts
|

Emotions associated with failed searches in a digital library

Abstract: Introduction. This paper discusses causes behind failed searches from the searchers’ perspective and examines associated emotions. Method. We conducted an online study with real users in their natural settings. Participants were asked to use a digital library and run one specific and one exploratory search task, using their own topics. They also answered pre- and post-questionnaires for both task types. Analysis. Three types of analysis were conducted: (i) one descriptive on answers in questionnaires, (ii) one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…They are provided with methodologies, methods and theoretical frameworks for studying exploratory search. Finally, this paper helps IS practitioners recognize the ubiquity of exploratory search activities in various ISs, for example, search engines (Khan et al , 2023; Pulikowski and Matysek, 2021), digital libraries (Barifah and Landoni, 2020; Hoeber and Shukla, 2022) and collaborative search systems (Andolina et al , 2018; Herceg et al , 2018). They can better appreciate the importance of certain design features in supporting exploratory search, thereby adapting their design strategies to develop exploratory search systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are provided with methodologies, methods and theoretical frameworks for studying exploratory search. Finally, this paper helps IS practitioners recognize the ubiquity of exploratory search activities in various ISs, for example, search engines (Khan et al , 2023; Pulikowski and Matysek, 2021), digital libraries (Barifah and Landoni, 2020; Hoeber and Shukla, 2022) and collaborative search systems (Andolina et al , 2018; Herceg et al , 2018). They can better appreciate the importance of certain design features in supporting exploratory search, thereby adapting their design strategies to develop exploratory search systems.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 18 years, exploratory search has been investigated from various perspectives, from information retrieval (IR) (Athukorala et al , 2016), information visualization (Hoeber and Yang, 2008), user interface design (Zhang et al , 2014) and collaborative search (González-Ibáñez et al , 2013), to specific application scenarios, for example, IR systems (Athukorala et al , 2016), search engines (Khan et al , 2023) and digital libraries (Hoeber and Shukla, 2022). The IS community has explored a number of research topics, such as discussing conceptual or theoretical frameworks of exploratory search (Marchionini, 2006; Savolainen, 2018), designing interfaces or IT artefacts that support exploratory search (Guo et al , 2023; Khan et al , 2023), evaluating exploratory search systems (Qu and Furnas, 2008; Zhang et al , 2014) and investigating factors that affect exploratory search performance in specific IS (Barifah and Landoni, 2020; Tang et al , 2013).…”
Section: Research Backgroundmentioning
confidence: 99%
“…One of the basic principles of libraries is to reinforce the autonomous behaviour of their users (Gorman, 2007). Moreover, the ideal scenario would be for users to have their expectations fulfilled when they perform a search by finding what they were looking for, as this would enhance the feeling of a successful search (Wilson, 1999;Barifah;Landoni, 2020).…”
Section: The Digital Library Interfacesmentioning
confidence: 99%
“…Windows Help needs to be accessed by the user, the time spent upon help and/or the user manual and the number of unmatched task executions within the real world [21]. It is concluded from other studies that the reaction time, i.e., that time interval between the request of a task and the response of the subject, can be considered with a response delay leading to a decreased rate of correct response [24]; [25]. The literature has shown that measures for performance can be undertaken through low-level metrics, i.e.…”
Section: Cognitive Load Metricsmentioning
confidence: 99%